Successful Endovascular Bailout Strategy for Retained Accunet Embolic Protection Device During Vertebral Artery Stenting - Sulhan, Suraj; Lyon, Kristopher; Lesley, Walter S. (Frontiers in Neurology, 2019)
Introduction Vertebral artery stenosis can lead to posterior circulation TIAs and stroke. Stenting is often performed to treat symptomatic vertebral artery stenosis. As with carotid stenting, embolic protection devices (EPD) are increasingly used when stenting a vertebral artery stenosis. In general, EPDs may rarely become detached or retained in the circulation during stent revascularization. We discuss a 77-year-old male with a history of cerebral atherosclerosis and prior left occipital lobe and right insular infarcts who presented with increasing left sided weakness and was found to have severe stenosis of the proximal left vertebral artery. We report the only known case and successful endovascular bailout for an irretrievable EPD occurring during vertebral artery stenting. Methods Systematic reviews of the medical literature were performed using PubMed and multiple combinations of keywords to search for irretrievable EPDs in either the carotid or vertebral arteries. The bibliographies of the results were used to identify additional publications until this process was exhausted. Results No prior reports were found for retained or detached vertebral artery EPD. A total of six cases were found where an EPD was lost in the carotid circulation. In three of the cases, a carotid arteriotomy was required to retrieve the EPD. In two other cases, diagnostic catheters were used to retrieve the EPD. In our case, an EverFlex Biliary Stent was used to flatten the irretrievable EPD into the vertebral artery wall while preserving robust vertebral artery perfusion. 21-month clinical and 16-month imaging follow-up demonstrated durable vertebral artery patency and no ischemic symptoms. Conclusion Successful bailout strategy for a retained vertebral artery EPD during stenting may be achieved with a self-expanding stent. The resultant revascularization remained durable and without clinical sequelae.